Social and Cultural Identity Pendekatan Face Negotation Theory dan Public Relations Multikulturalism Negara Jerman-China dan Indonesia - Dasrun Hidayat (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2014)
Research examines the focus of social identity and cultural identity of individuals between states of Germany, China and Indonesia. Building a sense of one's cultural identity is comprised of various identities that are interconnected with face negotiation theory perspective. Research constructive significance intersubjective phenomenology with qualitative constructivist paradigm. The study found that the inter-state identity constructed in a different manner. Germany builds social identity because of the role of government not of the family. Germany does not take into account the family so that the identity of individual awakes more independent. Chinese social identity constructed by social status, stratum or class. China still sees a group of men as dominant and women as a minority. Socially constructed male identity as it is considered more capable than women. Social identity of opposites so that social structures are built are also different. Similarly, Indonesia, social identity is built almost the same as China, only differentiating factor lies in obedience to carry out the norms and values prevailing in the social strata. Indonesia and China still uphold the cultural dimension of collectivity than Germany Individual dimensions. Using multicultural Public Relations function approach finally be able to recognize the cultural identity of each country and each social identity